ПУБЛІЧНА ПОЛІТИКА РЕІНТЕГРАЦІЇ ЗВІЛЬНЕНИХ ОБОРОНЦІВ УКРАЇНИ: ОСВІТНІЙ КОМПОНЕНТ ТА УПРАВЛІНСЬКІ МЕХАНІЗМИ РЕАЛІЗАЦІЇ - Майя Семко (Публічне управління і право: історія, теорія, практика, 2026)
The article examines the public policy of reintegration of discharged defenders of Ukraine through the educational component as a tool for restoring human capital, professional agency and civic participation of veterans. The relevance of the topic is determined by the scale of the transition from military service to civilian life, the need to coordinate veteran, educational, social, economic and regional policies, and the need to transform existing benefits into a manageable system of effective services. The purpose of the article is to substantiate a conceptual model for implementing the educational component of reintegration and to identify managerial mechanisms capable of ensuring its sustainability, accessibility and accountability. The methodological basis includes systemic, institutional, problem-oriented and comparative approaches; the study uses analysis of legal acts, strategic documents, official resources of public authorities, analytical materials of the Ukrainian Veterans Fund and international practices of educational support for veterans. It is argued that education in veteran policy should be understood not only as a social guarantee or compensatory privilege, but as an integrated public service combining career guidance, recognition of military experience, short modular programmes, formal education, career support, digital services, mental health support and partnership with employers. The article proposes a multilevel management model: the strategic level defines goals and standards; the interagency level ensures coordination; the regional level adapts services to community needs; the service level supports the veteran according to a “single route” principle; and the monitoring level evaluates outcomes through indicators of accessibility, completion, employment and satisfaction. Further research should focus on developing a methodology for evaluating educational programmes, studying regional models of veteran support and designing mechanisms for recognising competences acquired during military service.